2003
DOI: 10.1186/1471-244x-3-12
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia is a frequent finding in adults with Asperger syndrome

Abstract: Background: Asperger syndrome (AS) is a neurodevelopmental disorder belonging to autism spectrum disorders with prevalence rate of 0,35% in school-age children. It has been most extensively studied in childhood while there is scarcity of reports concerning adulthood of AS subjects despite the lifelong nature of this syndrome. In children with Asperger syndrome the initiation and continuity of sleep is disturbed because of the neuropsychiatric deficits inherent of AS. It is probable that sleep difficulties are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 21 publications
8
75
2
Order By: Relevance
“…We have reported a high prevalence of insomnia in AS adults assessed with a sleep questionnaire [8] and sleep diary [9]. The experience of insomnia may be associated with objective alteration of sleep architecture or, alternatively, with deviant perception of sleep due to psychological factors [10].…”
Section: Introductionmentioning
confidence: 99%
“…We have reported a high prevalence of insomnia in AS adults assessed with a sleep questionnaire [8] and sleep diary [9]. The experience of insomnia may be associated with objective alteration of sleep architecture or, alternatively, with deviant perception of sleep due to psychological factors [10].…”
Section: Introductionmentioning
confidence: 99%
“…Comorbidity of ASD and sleep problems increases the risk of mood disorders, such as anxiety and depression (Tani et al, 2003). We tested the possibility of a mediating effect of anxiety and depressive symptoms on the association between sleep quality and discordant peer relationships but we did not find evidence of mediation in any of the tested models.…”
Section: Discussionmentioning
confidence: 97%
“…1,2 In the study by Tuisku et al, an increased daytime motor activity in the lower limbs was found in AS adults. 3 This finding raises an interesting question as to whether these patients would also display periodic leg movements during sleep (PLMS) or other abnormal motor phenomena during sleep.…”
Section: Letter To the Editormentioning
confidence: 99%
“…All AS patients fulfilled the DSM-IV criteria for chronic insomnia. 1 The control group consisted of healthy volunteers with no complaints of sleep problems. 1 In the AS group, 29% (4/14) and in controls, 33% (3/9) were female.…”
Section: Letter To the Editormentioning
confidence: 99%
See 1 more Smart Citation